A study of barriers to online learning in distance education in China - Wang, Qifu (2013)
China's 'Modern Distance Education' is a government-led initiative prompted by the need to widen access to higher education and by the opportunities offered by the development of a widespread infrastructure of information and communications technologies. Distance education using television, radio and other technologies has a long history in China, but the advent of computer communications opened new possibilities for promoting educational development and the policy goal of modernisation. Distance education in China now involves online learning, to various degrees. However, the effectiveness of online courses depends on learners accessing them and using the resources provided. Does this happen? How well do learners manage their online learning? What barriers do they encounter? This thesis examines these questions through a study of adult distance learners based on analysis of a survey of 2931 learners and in-depth interviews with 21 learners and distance education experts in several locations. I find that: (1) The barriers to online learning faced by the sample learners are of seven types: communication and interaction; teaching and courses; learning resources; learning support services; external support and economic burdens; computer and network operation skills; and conditions for accessing the Internet. (2) Among the seven types of barrier, the 'communication and interaction' barrier is not only acting as the most important one faced by these learners, but also exists as a markedly independent one. (3) Improvements in 'communication and interaction' are the most effective in overcoming the other barriers and also contribute to increasing the learners' learning efficiency. This leads to the perception that working on 'communication and interaction' is very likely to be the best starting point for tackling barriers to online learning. According to these findings, I believe that if the situation of 'communication and interaction' in online learning can be improved for online learners to meet their desire for 'sociability', and once they can thus establish their own 'learning communities' and form relatively stable 'student-to-student' relationships, and 'student-to-teacher' relationships, other learning barriers will be reduced as well. Hence, I argue that we should always pay attention to making 'communication and interaction' occur effectively for online learners in the learning process. We should consider the matter of 'interaction' not only in the delivery process of teaching and tutoring as well as in learning activities, but also in the production of teaching materials and in the provision of learning materials, as well as in the building of learning environments. In a word, it is necessary to put the whole matter of 'interaction' at the core of the instructional system design for online learning.